2020
DOI: 10.1155/2020/6543593
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Blimp-1 and PD-1/PD-L1 Immune Checkpoint in an Autoimmune Thyroiditis Animal Model

Abstract: Objective. B lymphocyte-induced maturation protein 1 (Blimp-1) and programmed cell death protein 1 (PD-1) have opposing roles in the development of T cells; however, the mechanism of autoimmune thyroiditis-(AIT-) associated abortion is unclear. e present study investigated the expression of Blimp-1 and PD-1/PD-ligand 1 (PD-L1) in AIT-associated pregnancy loss and elucidated the related signaling pathway involving in the inflammatory response. Methods. An experimental fetal loss model with autoimmune thyroiditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Bcl-6 inhibits Blimp-1 and transcription factors of Th1, Th2, and Th17 cells (T-bet, GATA3, and RORγt) to maintain Tfh differentiation 208 , 209 ; Blimp-1 downregulates Bcl-6 and PD-1, inhibiting Tfh differentiation. 209 , 210 ICOS is induced by CD28-CD80/CD86 costimulation and plays an important role in Tfh differentiation by binding to its ligand ICOSL. 211 Studies have shown that ICOS-induced PI3K plays an important role in Tfh differentiation.…”
Section: Differentiation Of Cd4 + T-cell Subsetsmentioning
confidence: 99%
“…Bcl-6 inhibits Blimp-1 and transcription factors of Th1, Th2, and Th17 cells (T-bet, GATA3, and RORγt) to maintain Tfh differentiation 208 , 209 ; Blimp-1 downregulates Bcl-6 and PD-1, inhibiting Tfh differentiation. 209 , 210 ICOS is induced by CD28-CD80/CD86 costimulation and plays an important role in Tfh differentiation by binding to its ligand ICOSL. 211 Studies have shown that ICOS-induced PI3K plays an important role in Tfh differentiation.…”
Section: Differentiation Of Cd4 + T-cell Subsetsmentioning
confidence: 99%
“… 1 These tentative factors have been found relating to lymphocytes development and autoimmune diseases. 3 , 4 However, how chromosome remodeling is involved in autoimmune diseases remains largely unknown. Chromodomain helicaseDNA binding protein 4 (CHD4), a newly identified transcription factor, contributes to transcriptional repression, chromatin organization, genomic stability, and cell development.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, early B cell factor 1 (EBF1), B lymphocyte‐induced maturation protein 1 (Blimp‐1), B‐cell lymphoma 6 protein (Bcl‐6), and histone deacetylases (HDACs) regulate B‐cell development, differentiation, and somatic hypermutation/class switch recombination (CSR) 1 . These tentative factors have been found relating to lymphocytes development and autoimmune diseases 3,4 . However, how chromosome remodeling is involved in autoimmune diseases remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%